Multivector Variate Distributions (2020)
A new family of multivariate distributions under elliptical models is proposed in this work. Several particular cases of this multivector variate distributions are obtained and a number of published multivariate distributions in other contexts are found as simple corollaries. An application of interest in finance is full derived and compared with the traditional methods. © 2020, Indian Statistical Institute.